Savings Defaults and Payment Delays for Cash Transfers : Field Experimental Evidence from Malawi - Brune, Lasse (Elsevier, 2018)
Financial products and transfer schemes are typically designed to improve welfare by helping individuals follow through on their intertemporal plans. We implement an artefactual field experiment in Malawi to test the ability of households to manage a cash windfall by varying whether 474 households receive a payment in cash or through direct deposit into pre-established accounts at a local bank. Payments are made immediately, with one day delay, or with eight days delay. Defaulting the payments into savings accounts leads to higher net deposits into bank accounts, an effect that persists for a number of weeks afterwards. However, neither savings defaults nor payment delays affect the amount or composition of spending, suggesting that households manage cash effectively without the use of formal financial products.